Use of a game theory model to simulate competition in next generation networks - Pereira, João Paulo (2018)
With game theory, we want to understand the effects of the interaction between the different players defined in our business case - Next generation access networks (NGNs). In the proposed games, the profit (outcome) of each operator (player) will be dependent not only on their actions, but also on the actions of the other operators in the market. This paper analyzes the impact of the price (retail and wholesale) variations on several output results: players’ profit, consumer surplus, welfare, costs, service adoption, and so on. For that, two price-setting games are played. Players’ profits and Net Present Value (NPV) are used as the payoff for the players in the games analyzed. We assume that two competing Fiber to the home networks (incumbent operator and new entrant) are deployed in two different areas. For the game-theoretic model, we also propose an adoption model use in a way that reflects the competition between players and that the variation of the services prices of one player has an influence on the market share of all players. In our model we also use the Nash equilibrium to find equilibrium - Proposed tools include a module to search the Nash equilibrium in the game.